Faktor-Faktor Yang Mempengaruhi Kecepatan Pengambilan Dokumen Rekam Medis Rawat Jalan RSUD dr. Soekardjo Kota Tasikmalaya 2014 - Eka Rahman Rahmah; Ida Wahyuni (STIKes Persada Husada Indonesia, 2015)
The speed of service is one thing that can shows good quality of service, as well as the provision ofmedical record documents. Medical record documents mandatory to be available at any time. Surveys conductedin dr. Soekardjo Hospital Kota Tasikmalaya found that the extraction of outpatient medical record documentsstill found some factor that affecting the speed of documents retrieval outpatient medical record. The purpose ofthis research is to determine the factors that affecting the speed of document retrieval in the outpatient medicalrecord dr. Soekardjo Hospital Kota Tasikmalaya. This research is descriptive qualitative study with aphenomenological approach. Data collected through in-depth interviews and observations. Informants are fourworkers filing outpatient and head of medical record taken by purposive sampling techniques.The resultsshowed that the factors that affected the retrieval of documents including outpatient medical record are: limitedhuman resources filing outpatient section, lack of development of ambulatory ability filing officer, limitedfacilities and infrastructure are appropriate in the outpatient filing, and discrepancy between impmentation andSOP. It is Suggested that Hospital would make an effort sto improve these factors so that the speed of documentretrieval service outpatient medical record can be improved.Keywords: factors, medical record document retrieval.